The Relationship of Sociodemographic Factors to The Level of Knowledge, Perceptions, and Attitudes of The Community About Pulmonary TB Disease in Barlingmascakeb, Central Java - Muttaqin, Cecep Darwis; Samodra, Galih; Kusuma, Khamdiah Indah (Universitas Muhammadiyah Surakarta, 2023)
Pulmonary tuberculosis remains a significant health concern in Indonesia, holding the second position globally. Central Java province alone contributes to 44% of all pulmonary tuberculosis cases in the country. This research endeavors to explore the correlation between sociodemographic factors and the community's knowledge, perceptions, and attitudes toward tuberculosis (TB) in Barlingmascakeb, utilizing a Cross-sectional approach. The study employed an online-based questionnaire via the Google Forms platform, reaching 438 respondents throughout Barlingmascakeb. The analysis involved univariate methods to interpret the characteristics of the Barlingmascakeb community's awareness of pulmonary TB, presented in percentage form. Additionally, bivariate analysis was conducted to ascertain connections, with results Adjusted for a significance level of p 0.05. The results indicated significant connections between the knowledge level and various variables, such as gender (p = 0.006), age (p = 0.000), occupation (p = 0.001), and district (p = 0.000). Additionally, there were correlations between perception and age (p = 0.006), highest educational attainment (p = 0.010), and district (p = 0.001). Likewise, attitudes were associated with age (p = 0.009), highest educational attainment (p = 0.020), and district (p = 0.015). This emphasizes the importance of comprehending the interplay between sociodemographic factors and individual attitudes in addressing pulmonary TB within the community.